Is palm kernel cake a suitable alternative feed ingredient for poultry? - Azizi, Mohammad Naeem; Loh, Teck Chwen; Foo, Hooi Ling; Lim, Eric Teik Chung (MDPI, 2021)
Palm kernel cake (PKC), a by-product of oil extracted from palm nuts through expeller press or solvent extraction procedures is one of the highest quantities of locally available and potentially inexpensive agricultural product. PKC provides approximately 14–18% of crude protein (CP), 12–20% crude fiber (CF), 3–9% ether extract (EE), and different amounts of various minerals that feasible to be used as a partial substitute of soybean meal (SBM) and corn in poultry nutrition. Poultry’s digestibility is reported to be compromised due to the indigestion of the high fiber content, making PKC potentially low for poultry feeding. Nevertheless, solid-state fermentation (SSF) can be applied to improve the nutritional quality of PKC by improving the CP and reducing CF content. PKC also contains β-mannan polysaccharide, which works as a prebiotic. However, there is a wide variation for the inclusion level of PKC in the broiler diet. These variations may be due to the quality of PKC, its sources, processing methods and value-added treatment. It has been documented that 10–15% of treated PKC could be included in the broiler’s diets. The inclusion levels will not contribute to a negative impact on the growth performances and carcass yield. Furthermore, it will not compromise intestinal microflora, morphology, nutrient digestibility, and immune system. PKC with a proper SSF process (FPKC) can be offered up to 10–15% in the diets without affecting broilers’ production performance.